Emergency department workforces’ experiences and perceptions of well-being from an international perspective: a scoping review - Damian Roland; Natalie Armstrong; Kate Kirk; Lucy Swancott; Helen L Walters (BMJ Open)
Objectives To identify and present the available evidence regarding workforce well-being in the emergency department.Design Scoping review.Setting The emergency department (ED).Data sources CINAHL, MEDLINE, APA PsycINFO and Web of Science were searched with no publication time parameters. The reference lists of articles selected for full-text review were also screened for additional papers.Eligibility criteria for study selection All peer-reviewed, empirical papers were included if: (1) participants included staff-based full-time in the ED, (2) ED workforce well-being was a key component of the research, (3) English language was available and (4) the main focus was not burnout or other mental illness-related variables.Results The search identified 6109 papers and 34 papers were included in the review. Most papers used a quantitative or mixed methods survey design, with very limited evidence using in-depth qualitative methods to explore ED workforce well-being. Interventions accounted for 41% of reviewed studies. Findings highlighted pressing issues with ED workforce well-being, contributed to by a range of interpersonal, organisational and individual challenges (eg, high workloads, lack of support). However, the limited evidence base, tenuous conceptualisations and links to well-being in existing literature mean that the findings were neither consistent nor conclusive.Conclusions This scoping review highlights the need for more high-quality research to be conducted, particularly using qualitative methods and the development of a working definition of ED workforce well-being.